Dealing with Guilt in Pastoral Care - Jenő KISS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2022)
This study starts from the current experiential reality of the family, described by sociologist Peter V. Zima as follows: The family, as a victim of society as an alienating structure, becomes itself an alienating structure, which makes it impossible to establish intimate and supportive relationships between family members and the future of the family. The family therefore fails to fulfil its original role of being a place of embeddedness and a resource for society. It is also hampered by transgressions while hindering the search for fairness towards each other. Pastoral care can help families to recognize the essence of guilt and then seek effective resources of help. The paper, therefore, highlights the fundamental relational nature of human existence and the existential nature of guilt through philosophical, theological, and biblical anthropology (1). It then highlights the importance of the notion of existential guilt in contextual perspectives, therapy, and pastoral care (2). Finally, following a theological interpretation of the concept of guilt, it identifies in four points the areas in which the use of the concept of existential guilt in pastoral care is helpful (3).